Synopsis of Bunchosia Kunth (Malpighiaceae) from the Atlantic Forest - de Almeida, Rafael Felipe; Pellegrini, Marco Octávio De Oliveira (Phytotaxa, 2016)
As part of the ongoing revision of Malpighiaceae from the Atlantic Forest, an extensive review of Vellozo’s Flora fluminensis and the names associated to the Bunchosia maritima complex was carried out. We conclude that seven species should be recognized, with four of them related to the morphological complex. Each of the seven species can be distinguished by the number of glands on the abaxial side of the leaf blade, venation pattern, inflorescence, androecium and drupe morphology, and number of carpels. Thus, we redefine B. maritima to a much narrower sense. In order to determine proper nomenclature for the recognized species, the typification of all names was investigated. We designate a lectotype and an epitype for B. maritima, a lectotype for B. apiculata and a neotype for B. fluminensis. Furthermore, we present an identification key for the Bunchosia species from the Atlantic Forest domain.